Screening 27 Genotypes of Eggplant (Solanum melongena) for Resistance to Three Species of Begomovirus - Dian Yogi Noviana; Rudi Hari Murti; Panjisakti Basunanda; Ratih Wahyuni; Mustika Ajeng Kartini Putri Pertiwi (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Three primary species of Begomovirus, Tomato yellow leaf curl Kanchanaburi virus (TYLCKaV), Pepper yellow leaf curl Indonesia virus (PepYLCIV), and Tomato leaf curl New Delhi virus (ToLCNDV), have significantly impacted eggplant production in Indonesia, with infections often involving multiple viruses causing severe symptoms. Utilizing resistant cultivars for these viruses is the most effective control method. This study aimed to identify resistant genotypes and evaluate the heritability of eggplant resistance to Begomovirus. In a controlled environment, 27 eggplant genotypes were inoculated with the single of three Begomovirus species separately (molecularly confirmed), using Bemisia tabaci as a vector. The plants were inoculated at the seedling growth stage and observed weekly until the disease progression stabilized. These assessments included monitoring symptoms, the number of symptomatic plants, and assigning disease severity scores to each individual. The data were analyzed using ANOVA and Tukey-HSD tests at α = 5%. The results indicated that EPA 21016 A genotype was resistant to TYLCKaV, with the lowest disease incidence (2.5%) and severity (1.25%), making it a promising parental line for breeding virus-resistant cultivars. However, all genotypes were susceptible to PepYLCIV and ToLCNDV, with a 100% disease incidence. High heritability for TYLCKaV resistance suggests its potential for early-generation selection, while low heritability for PepYLCIV and ToLCNDV indicates the need for enhanced genetic variability.